منهج دراسة قضايا المرأة بين تفسير الشعراوي وتفسير الأزهر : دراسة مقارنة - Norbani binti Ismail (Kuliyyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2005)
The research attempts to identify the methods of studying women issues by two exegetes (al-mufassirin): Egyptian Muhammad Mutawalli al-Sha'rawi (1911-1998) and Indonesian Professor Äamka (1908-1981). The study is based on the historicaldescriptive method which rests on the assumption that economic, political and social conditions influence the methods of the exegesis. The researcher started this dissertation by exploring the conditions of women in Egypt and Indonesia during the times of the two scholars. By referring to their writings and to some classical works of Tafsir and Hadith dealing with issues of equality, polygamy, divorce, veiling and clothing, career and family planning, the research finds that both al-Shaykh alSha‛rāwi and Prof Hamka relied on methods of Tafsir bi al-Ma'thur (exegesis based on reports narrated by Prophet Muhammad (peace be upon him), his Companions and Successors) and Tafsar bi al-Ra'y (exegesis based on intellectual judgment). The dissertation also confirms the assumption that economic, political and social conditions have strong relationships with the responses of the two scholars. The study also concludes that methods of studying women issues in the exegesis of al-Shaykh alSha'rawi and Professor Hamka are based on the following foundations: refuting unfounded claims on women issues, minimising the Tafsir bi al-Ma'thur, interpreting the Qur'an on the basis that it is the prime source that deals with women issues, emphasizing the inimitability (I‛jaz) of the Qur'an in the exegesis, applying different ways to interpret the Qur'an on women issues, avoiding the lengthy discussion on legal disagreements, protecting the positions and rights of women in accordance with the Qur'anic perspective, comparing between Islamic and non-Islamic teachings in explaining the Qur'an, highlighting the flexibility of the Qur'anic teachings and concerning with the order of the social life of women. However, this study finds that the methods of both exegeses differ in one foundation; Professor Hamka declared clearly his rejection of citing the Isra'iliyyat (narrations of Jewish-Christian origin) while al-Shaykh al-Sha‛rawi did not clearly state his stance towards this issue.